THE PHENOMENON OF DRUG AND PSYCHOTROPIC SUBSTANCE ABUSE - TRADITIONAL AND DIGITAL - CAUSES, EFFECTS, SOLUTIONS - Taha , Dr. Shaima Ibrahim; Dr. Saddam Ali Hadi (Antis Publisher, 2024)
The problem of traditional drug abuse and addiction is one of the most dangerous problems and negative phenomena that contemporary and backward societies suffer from, because it is a source of concern and threat to their children at all social, economic, cultural and security levels. It is also a hidden weapon in wars and one of the methods of black psychological operations that hostile countries use and resort to influence the youth and penetrate their minds and thoughts and change their behavior and attitudes to control them and achieve their goals. In addition to a new and innovative type of drugs, namely digital drugs, which have recently spread in conjunction with scientific progress in the field of information and communications technology, and in which criminals rely on creating applications and programs that lead to a type of anesthesia when heard. The importance of our research comes from the great danger of drug abuse, which negatively affects all aspects of individuals' lives. Combating this negative phenomenon is a necessity to confront the challenges associated with it, which contributes to building a safer and healthier society. The exacerbation of the problem of the spread of drugs in all their forms in the world, especially in recent decades, has constituted one of the most important security challenges facing society, which requires a single and serious stand for work, joint cooperation and coordination of all international efforts. And the national to combat and treat this negative phenomenon.